tsRNA, cell death and disease: Connecting the dots - Xiaoyu Ma; Jiesi Xu; Guoping Li (Non-coding RNA Research)
Cell death is essential for maintaining physiological homeostasis and regulating pathological processes. tRNA-derived small RNAs (tsRNAs), an emerging non-coding small RNA, play key roles in a various form of cell death. The relationship between tsRNAs and diseases has attracted growing attention. However, many challenges remain, particularly in understanding how tsRNAs regulate cell death and their newly discovered roles in these pathways. This paper reviews the generation and classification of tsRNAs and their roles in different diseases through cell death processes, such as ferroptosis, apoptosis, necroptosis, autophagy and pyroptosis. We discuss in detail the dysregulation of tsRNA expression in neurological disorders, metabolic diseases and cancer. We highlight the potential of tsRNAs as biomarkers and therapeutic targets in the context of cell death pathways.